Signal transducer and activator of transcription (STAT) signalling and T-cell lymphomas - Mitchell, Tracey J (Blackwell Science Inc, 2005)
Interaction of cytokines with their cognate receptors leads to the activation of latent transcription factors – the signal transducers and activators of transcription (STAT) proteins – whose biological activities ultimately regulate many critical aspects of cell growth, survival and differentiation. Dysregulation of the JAK-STAT pathway is frequently observed in many primary human tumours, reflecting the importance of this pathway in the maintenance of cellular integrity. Here we review the current progress in STAT structure and function, and the contribution of STAT signalling to the pathogenesis of T-cell lymphomas.